Development of a Sensitive Escherichia coli Bioreporter Without Antibiotic Markers for Detecting Bioavailable Copper in Water Environments - Pang, Yilin; Ren, Xiaojun; Li, Jianghui; Liang, Feng; Rao, Xiaoyu; Gao, Yang; Wu, Wenhe; Li, Dong; Wang, Juanjuan; Zhao, Jianguo; Hong, Xufen; Jiang, Fengying; et al. (Frontiers in Microbiology, 2020)
The whole-cell bioreporters based on the cop-operon sensing elements have been proven specifically useful in the assessment of bioavailable copper ions in water environments. In this study, a series of experiments was conducted to further improve the sensitivity and robustness of bioreporters. First, an Escherichia coli △copA△cueO△cusA mutant with three copper transport genes knocked out was constructed. Then, the copAp::gfpmut2 sensing element was inserted into the chromosome of E. coli △copA△cueO△cusA by gene knock-in method to obtain the bioreporter strain E. coli WMC-007. In optimized assay conditions, the linear detection range of Cu2+ was 0.025-5 mg/L (0.39 to 78.68 μM) after incubating E. coli WMC-007 in LB medium for 5 h. The limit of detection (LOD) of Cu2+ was 0.0157 mg/L (0.25 μM). Moreover, fluorescence spectrometry and flow cytometry experiments showed more environmental robustness and lower background fluorescence signal than those of the sensor element based on plasmids. In addition, we found that the expression of GFPmut2 in E. coli WMC-007 was induced by free copper ions, rather than complex-bound copper, in a dose-dependent manner. Particularly, the addition of 40 mM MOPS buffer to E. coli WMC-007 culture enabled accurate quantification of bioavailable copper content in aqueous solution samples within a pH range from 0.87 to 12.84. The copper recovery rate was about 95.88%-113.40%. These results demonstrate potential applications of E. coli WMC-007 as a bioreporter to monitor copper contamination in acidic mine drainage, industrial wastewater and drinking water. Since whole-cell bioreporters are relatively inexpensive and easy to operate, the combination of this method with other physicochemical techniques will in turn provide more specific information on the degree of toxicity in water environments.